2016
DOI: 10.1167/iovs.16-19171
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Inner Retinal Spots With Inverted Reflectivity on En Face Optical Coherence Tomography in Diabetic Retinopathy

Abstract: Citation: Yoza R, Murakami T, Uji A, et al. Characterization of inner retinal spots with inverted reflectivity on en face optical coherence tomography in diabetic retinopathy. Invest Ophthalmol Vis Sci. 2016;57:186257: -187057: . DOI:10.1167 PURPOSE. The purpose of this study was to characterize inner retinal spots with inverted reflectivity on en face images of swept-source optical coherence tomography (SS-OCT) in diabetic retinopathy (DR). METHODS.We retrospectively reviewed seventy-five eyes of 75 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Second, we evaluated only the cross-sectional OCT images that passed vertically through the fovea. Recently, Yoza et al reported that the spots with inverted reflectivity in the RNFL and ganglion cell layer in the en face SS-OCT images in a 6×6 mm areas were associated with the disruption of the neurovascular units in diabetic retinopathy 29. Therefore, prospective studies with contiguous OCT scans of the macular region may be able to evaluate the relationship between the OCT findings and the presence of retinal non-perfused areas more accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we evaluated only the cross-sectional OCT images that passed vertically through the fovea. Recently, Yoza et al reported that the spots with inverted reflectivity in the RNFL and ganglion cell layer in the en face SS-OCT images in a 6×6 mm areas were associated with the disruption of the neurovascular units in diabetic retinopathy 29. Therefore, prospective studies with contiguous OCT scans of the macular region may be able to evaluate the relationship between the OCT findings and the presence of retinal non-perfused areas more accurately.…”
Section: Discussionmentioning
confidence: 99%
“…26 Another OCT finding in the inner retinal layers, the spot with inverted reflectivity on OCT images using the Optovue RTVue XR Avanti, also was evaluated according to modified methods as described previously. 27 We sometimes found welldefined spots with lower reflectivity in the NFL and higher reflectivity in the GCL/IPL in the sNPA, after the en face OCT images in the NFL or GCL were constructed using the manual setting of the inner and outer borders of these layers in the localized areas. When the boundary between the GCL and IPL was indefinite, we constructed en face images from the inner border of the GCL to the center of the GCL/IPL to evaluate the patchy lesions in the GCL.…”
Section: Optical Coherence Tomographymentioning
confidence: 88%
“…Intriguingly, the sNPA had inner retinal lesions, that is, inner retinal spots with inverted OCT reflectivity and no boundary between the NFL and GCL/IPL. 26,27 The dNPA was accompanied frequently not only by neuroglial changes in the corresponding layer, that is, cystoid spaces, but also by morphologic changes in other layers. These data suggested the clinical feasibility of a three-dimensional evaluation of the disruption in the neurovascular units in DR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations